Gas separation membrane and gas separation membrane module
The gas separation membrane addresses the issues of heat and chemical resistance by using a matrix with high carbon content and additive particles with higher elastic modulus, resulting in improved durability and separation performance.
Patent Information
- Application Number
- JP2021157463
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-05
- Filing Date
- 2021-09-28
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-09-28
AI Technical Summary
Existing gas separation membranes face challenges with insufficient heat resistance and chemical resistance, leading to instability and gas leakage during long-term operation.
A gas separation membrane with a separation functional layer composed of a matrix with a carbon element ratio of 70 atomic% or more, combined with additive particles having a higher elastic modulus, where the carbon element ratio difference between the matrix and additive particles is 30% or less.
The membrane exhibits enhanced heat resistance, chemical resistance, and durability, maintaining excellent separation performance over a long period without damage or gas leakage.
Smart Images

Figure 0007666268000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas separation membrane and a gas separation membrane module. [Background technology]
[0002] Membrane separation is known as a method for selectively separating and purifying specific components from various mixed gases. Compared to other separation and purification methods, membrane separation utilizes pressure and concentration differences, and therefore consumes less heat energy, making it an energy-saving method that has attracted attention. On the other hand, gas separation processes require heat and chemical resistance, and there have been challenges in providing a stable supply of gas separation membranes that meet these requirements. [Prior art documents] [Patent documents]
[0003] Patent Document 1 describes a separation membrane made of a polymer matrix and a nonwoven fabric of carbon nanotubes.
[0004] Patent Document 2 discloses a material containing carbon as a matrix and various materials added as reinforcing materials. [Patent Document 1] JP 2014-237127 A [Patent Document 2] Special Publication No. 2011-527231 Summary of the Invention [Problem to be solved by the invention]
[0005] The separation membrane disclosed in Patent Document 1 was able to ensure mechanical durability by reinforcing the polymer matrix with a nonwoven fabric, but due to the low heat resistance of the polymer matrix, its heat resistance as a gas separation membrane was insufficient.
[0006] The separation membrane disclosed in Patent Document 2 has the problem that simply combining the matrix and reinforcing material makes it prone to peeling at the interface, causing breakdown during long-term operation and making stable operation impossible due to gas leakage.
[0007] An object of the present invention is to provide a gas separation membrane and a gas separation membrane module that have heat resistance and chemical resistance and can stably exhibit excellent separation performance for a long period of time. [Means for solving the problem]
[0008] In order to solve the above problems, the gas separation membrane of the present invention has the following configuration.
[0009] A gas separation membrane having a separation functional layer at least in a portion thereof, The separation functional layer is composed of a matrix and additive particles, the matrix is made of a carbonized polymer compound, The carbon element ratio of the matrix is 70 atomic % or more, The gas separation membrane is characterized in that, when the carbon element ratio of the matrix is X (atomic %) and the carbon element ratio of the additive particles is Y (atomic %), (|XY| / X) × 100 is 30% or less.
[0010] In the gas separation membrane of the present invention, it is preferable that the additive particles have a higher elastic modulus than the matrix.
[0011] The gas separation membrane of the present invention is preferably a composite membrane.
[0012] In the gas separation membrane of the present invention, the additive particles are preferably made of an inorganic material.
[0013] In the gas separation membrane of the present invention, the additive particles preferably have an average aspect ratio of 10 or more.
[0014] In the gas separation membrane of the present invention, the content of the additive particles in the separation functional layer is preferably 10% by volume or less.
[0015] The gas separation membrane of the present invention preferably has a hollow fiber shape. Effect of the Invention
[0016] The present invention provides a gas separation membrane and a gas separation membrane module which are capable of suppressing damage to the gas separation membrane, having heat resistance and chemical resistance, and capable of stably exhibiting excellent separation performance for a long period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention relates to a gas separation membrane having a separation functional layer at least in a portion thereof, the separation functional layer being composed of a matrix and additive particles, the carbon element ratio of the matrix being 70 atomic % or more, and when the carbon element ratio of the matrix is X (atomic %) and the carbon element ratio of the additive particles is Y (atomic %), (|XY| / X) × 100 is 30% or less.
[0018] <Gas separation membrane> The gas separation membrane of the present invention has a separation functional layer at least in a part thereof. "Having a separation functional layer at least in a part of the gas separation membrane" refers to a state in which a layered part having a separation function (separation functional layer) forms at least a part of the material, and the part where the separation functional layer is not formed may be in a state in which the flow of gas can be controlled as a part without a separation function. "A state in which the flow of gas can be controlled" refers to a state in which gas is substantially not permeable, and is a state in which the permeability of nitrogen gas is 0.01 nmol / (m 2 This means that the viscosity is less than sPa.
[0019] The separation functional layer constituting the gas separation membrane of the present invention is composed of a matrix and additive particles. The matrix in the separation functional layer refers to the sea part of the so-called sea-island structure, where the carbon element ratio X is 70 atomic % or more and 100 atomic % or less. The additive particles in the separation functional layer refer to the island part of the so-called sea-island structure, where the carbon element ratio Y is 60 atomic % or more and 100 atomic % or less, and where the carbon element ratio Y is a value different from the carbon element ratio X.
[0020] Here, the separation functional layer has a sea-island structure, and how the carbon element ratio is distributed, that is, whether the separation functional layer has a matrix and additive particles, can be determined by converting the carbon element mapping image of the separation functional layer into a binary image by discriminant analysis and comparing the binary data with the carbon element mapping image. In other words, the part that forms the sea and has a carbon element ratio of 70% or more and 100 atomic% or less is defined as the matrix. Then, when the average value of the carbon element ratio of the matrix part in the carbon element mapping image is X, the part other than the matrix, that is, the carbon element ratio of the island is Y (atomic%), and the part where Y is 60 atomic% or more and 100 atomic% or less is defined as the additive particle. Note that when the carbon element ratio X and the carbon element ratio Y are the same, they cannot be distinguished by binarization, so if the sea part and the island part can be recognized by binarization, it can be determined that the carbon element ratio X and the carbon element ratio Y are different values.
[0021] Ma The larger the carbon element ratio X of the triplex, the better the film performance, chemical resistance, and heat resistance, and it is more preferable that the carbon element ratio X is 80 atomic % or more. stomach.
[0022] On the other hand, since the smaller the carbon content, the more flexible and resistant to breakage the matrix is, and therefore the longer-term durability is improved, the carbon element ratio X of the matrix is preferably 99 atomic % or less, and more preferably 92 atomic % or less.
[0023] The constituent elements of the matrix other than carbon are not particularly limited, but may contain hydrogen, oxygen, nitrogen, boron, sulfur, silicon, etc., and may also contain alkali metals, alkaline earth metals, etc. The above element ratios are determined by various analytical methods, and can be analyzed using energy dispersive X-ray spectrometry, etc.
[0024] Furthermore, as the carbon material used for the matrix, from the viewpoint of easy control of the carbon element ratio X of the matrix described above, a carbide of a polymer compound is used. The purpose is to For example, the resin may be obtained by baking a polymer material containing at least one of the above-mentioned thermoplastic resins and thermosetting resins. In particular, it is preferable to select phenol resin, polyacrylonitrile, polyimide, etc.
[0025] Here, having a separation function refers to having the function of generating a difference in the permeation rate for gases, and refers to a separation factor of 1.2 or more based on the permeation rate ratio between CO2 and CH4 (CO2 / CH4).
[0026] The additive particles used in the gas separation membrane of the present invention, when combined with a matrix, have the effect of suppressing damage to the separation functional layer. In addition, as long as the additive particles can exert the effect of suppressing damage to the separation functional layer, it is also a preferred embodiment that the additive particles further have a function of permeating gas or a function of separating gas.
[0027] In addition, in the separation functional layer constituting the gas separation membrane of the present invention, it is preferable that the additive particles have a higher elastic modulus than the matrix. When the additive particles have a higher elastic modulus than the matrix, the effect of preventing the destruction of the separation functional layer when combined is exerted, and therefore, the effect of preventing damage during operation as a gas separation membrane and enabling stable use for a long period of time is obtained.
[0028] Here, the elastic modulus of the additive particles is higher than that of the matrix, meaning that when the elastic modulus of the matrix is taken as 1.0, the elastic modulus ratio (elastic modulus of additive particles / elastic modulus of matrix) is 10 or more. The higher the elastic modulus of the additive particles, the easier it is to obtain a reinforcement effect and prevent breakage, so it is preferably 100 or more, more preferably 250 or more, and even more preferably 400 or more. There is no particular need to set an upper limit for the elastic modulus ratio, but since the lower the elastic modulus ratio, the more flexibly the particles deform, and the more easily they can absorb instantaneous impact forces, it is more preferable that the elastic modulus ratio (elastic modulus of additive particles / elastic modulus of matrix) is 5,000 or less.
[0029] The elastic modulus ratio is defined as the ratio of the elastic modulus between the point showing the highest elastic modulus and the point showing the lowest elastic modulus in the elastic modulus mapping image observed in an area of 1 μm × 1 μm by performing elastic modulus mapping analysis on the cross section of the separation functional layer using an atomic force microscope, and the point showing the lowest elastic modulus and forming a sea is defined as the elastic modulus of the matrix. The elastic modulus ratio in the present invention is defined as the average value of the ratio of the elastic modulus analyzed at each observation point by changing the location of 10 or more samples.
[0030] The material of the additive particles used in the gas separation membrane of the present invention is not particularly limited as long as it can exert the above-mentioned effect. The closer the carbon element ratio Y of the additive particles is to the carbon element ratio X of the matrix, the better the adhesion with the matrix and the tendency to improve the strength is observed. From this viewpoint, (|XY| / X)×100, which is an index of the closeness of the carbon element ratio between the matrix and the additive particles, is 30% or less. (|XY| / X)×100 is preferably 20% or less, and more preferably 0% or more and 10% or less. Here, the constituent elements other than carbon are not particularly limited on the premise that the above-mentioned effect is exerted, but may contain oxygen, nitrogen, boron, sulfur, silicon, etc., and may also contain alkali metals, alkaline earth metals, etc. The above element amounts are analyzed by applying energy dispersive X-ray spectroscopy or the like to a transmission electron microscope capable of observing microscopic parts of the matrix and the additive, and appropriately adjusting so that signals are detected so that the element ratios can be calculated for all elements except hydrogen element.
[0031] As described above, the carbon element ratio Y of the additive particles used in the gas separation membrane of the present invention is 60 atomic% or more and 100 atomic% or less. Since the higher the carbon element ratio Y, the better the membrane performance, chemical resistance, and heat resistance, it is preferably 70 atomic% or more, and more preferably 80 atomic% or more. On the other hand, since the lower the carbon element ratio, the more flexible and resistant to breakage tends to increase, and therefore the effect of preventing breakage of the membrane that ensures long-term durability is improved, the carbon element ratio Y of the additive particles is more preferably 99 atomic% or less, and even more preferably 90 atomic% or less.
[0032] The additive used in the gas separation membrane of the present invention can be selected from various materials such as polymeric materials, biological materials, inorganic materials, etc., and can be used alone or in combination of two or more. When the additive of the present invention is a polymeric material, examples of the additive include polyester, polyamide, polyimide, polyether, polyphenylene sulfide, polyether ether ketone, and copolymers mainly composed of these.
[0033] The additive particles used in the gas separation membrane of the present invention are preferably inorganic materials. Inorganic materials tend to have a high elastic modulus, so that they are likely to exhibit a reinforcing effect when combined with a matrix, and also tend to have high heat resistance and chemical resistance. The inorganic material is not particularly limited as long as it satisfies the carbon element ratio, and examples thereof include carbon compounds such as silicon carbide, boron carbide, and carbon nitride, and materials mainly composed of carbon elements. These materials may be used in combination, such as in a state where the surface of the material is coated with carbon in order to satisfy the carbon element ratio.
[0034] In addition, among the additive particles in the separation functional layer constituting the gas separation membrane of the present invention, the material mainly composed of carbon element is preferably one or more selected from the group consisting of carbon black, graphite, expanded graphite, carbon nanohorn, carbon nanoribbon, carbon nanotube, graphene, graphene oxide, and fullerene. These materials are easy to make the carbon element ratio close to that of the matrix, so that they are easy to express the reinforcing effect when combined with the matrix. In addition, among these materials, from the viewpoint of having a large specific surface area and easily increasing the adhesive interface that expresses the reinforcing effect of the matrix constituting the separation functional layer by the additive particles, it is more preferable to be one or more selected from the group consisting of carbon black, carbon nanohorn, carbon nanoribbon, carbon nanotube, graphene, graphene oxide, and fullerene, and it is even more preferable from the viewpoint of cost.
[0035] In addition, among the additive particles contained in the separation functional layer constituting the gas separation membrane of the present invention, it is preferable to include an additive having an average aspect ratio of 10 or more. Since a large average aspect ratio makes it easier to obtain a combined effect between the matrix and the additive particles, the average aspect ratio of the additive particles is more preferably 300 or more, even more preferably 800 or more, and particularly preferably 1,500 or more. In addition, there is no particular need to set an upper limit on the average aspect ratio of the additive particles, but from the viewpoint of easily finely dispersing the additive particles in the separation functional layer and being able to form a uniform separation functional layer while ensuring the fluidity of the liquid, particularly when forming the separation functional layer using a liquid, it is preferable that the average aspect ratio of the additive particles in the separation functional layer is 2,000 or less. Here, the average aspect ratio is the length L of the shortest part of the additive particles dispersed in the matrix, which is obtained by taking one particle of the additive particles dispersed in the matrix by three-dimensional microscopic photography and taking the three-dimensional data of the particle. s and the length of the longest part L l Ratio to (L l / L s The average value of the values calculated by taking the length of the shortest part L sFor example, in the case of graphene, it generally corresponds to the thickness of the thinnest part, and in the case of carbon nanotubes, it corresponds to the diameter of the thinnest part. Also, the length L of the longest part corresponds to the thickness of the thinnest part. l For graphene, the measurement is performed by extracting and measuring the part of the flat plate shape where the longest distance can be measured based on the edge, and for carbon nanotubes, the measurement corresponds to the length from one end to the other of a bent carbon nanotube. The three-dimensional microscope photography is not particularly limited as long as it is possible to separate and observe the matrix and additive particles, but it is preferable to appropriately select an analysis method that can separate, observe, and analyze the matrix and additive particles as electronic information, such as slice & view, which cuts out a cross section with an ion beam and continuously observes it with a scanning electron microscope, or a method of applying computer tomography using a transmission electron microscope.
[0036] The surface of the additive particles used in the gas separation membrane of the present invention may be chemically modified with a carboxyl group, an amide group, or the like, which is preferable because the adhesiveness to the matrix is further improved by chemical bonding. On the other hand, the fewer the surface functional groups of the additive particles, the more improved the chemical resistance. Therefore, it is preferable that the ratio of O=CO components derived from carboxyl groups and O=CN components derived from amide bonds to the total bond components of carbon elements is 0.1% to 30%.
[0037] The additive particles in the separation functional layer of the present invention may be one type or two or more types in combination. Depending on the application, other additive particles may be included within a range that does not impair the purpose of the present invention, but the material with a carbon element ratio of less than 60 atomic % is preferably added in an amount of less than 50 volume % of the additive particles of the present invention, and more preferably less than 20 volume %.
[0038] The size of the additive particles in the separation functional layer is not particularly limited, but the length Ls of the shortest part is preferably 0.3 nm or more and 10 μm or less. When Ls is 0.3 nm or more, the handling is easy while securing a sufficient specific surface area. On the other hand, when Ls is 10 μm or less, the specific surface area is large and the adhesion to the matrix is improved, so that the strength of the separation membrane is improved. From the above viewpoint, Ls of the additive particles is preferably 0.3 nm or more and 1 μm or less, and more preferably 1 nm or more and 100 nm or less.
[0039] The content of additive particles in the separation functional layer constituting the gas separation membrane of the present invention is not particularly limited, but is preferably 10% by volume or less in 100% by volume of the separation functional layer, since the matrix reinforcing effect can be sufficiently obtained. If the content of additive particles is low, the dispersion of the additive particles in the matrix is improved, and a separation functional layer with excellent thickness uniformity can be obtained. On the other hand, if the content is high, the content of additive particles per unit volume of the separation functional layer increases, and the reinforcing effect is easily expressed, and the strength of the separation functional layer is improved. From these viewpoints, the content of additive particles in the separation functional layer is more preferably 0.3 to 9% by volume, and even more preferably 0.5 to 5% by volume.
[0040] Here, the content of additive particles in the separation functional layer constituting the gas separation membrane of the present invention is calculated by determining the volume from the three-dimensional data of the additive particles extracted by the three-dimensional microscopic photography of the separation functional layer described above. Note that, taking into consideration the variation, data containing 10 or more additive particles is used, and when obtaining the three-dimensional data of the separation functional layer, the observation field is taken so that 10 or more additive particles are included in the observation field, and the volume ratio of the additive particles to the volume of the separation functional layer within the observation field is taken as the content (volume %) of the additive particles in the separation functional layer.
[0041] In the separation functional layer constituting the gas separation membrane of the present invention, the volume ratio of additive particles that are present apart from other additive particles is preferably 1 volume % or more, more preferably 5 volume % or more, of the total volume of all additive particles. When the volume ratio of additive particles that are present independently without contacting other additive particles is within the above preferred range, the combined effect of the matrix and the additive particles is easily obtained.
[0042] Here, in the gas separation membrane of the present invention, the volume percentage of additive particles that do not come into contact with other additive particles and exist independently is determined by identifying additive particles that do not come into contact with other additive particles and exist independently from the three-dimensional data of the additive particles extracted by three-dimensional microscopic photography of the separation functional layer described above, and determining their volume percentage. Note that, taking into consideration the variation, data that contains 100 or more additive particles is used, and if there are not 100 or more additive particles in one data, data obtained from another observation field is added, and the separation functional layer containing a total of 100 or more additive particles is observed to determine the volume percentage.
[0043] Among the additive particles that exist independently and are not in contact with other additive particles, it is preferable to include additive particles with an aspect ratio of 10 or more, as this makes it easier to increase the adhesive interface that exerts the strengthening effect of the matrix that constitutes the separation functional layer by the additive particles.
[0044] The thickness of the separation functional layer of the present invention is not particularly limited, but a thicker layer is preferable because it is more resistant to damage caused by external forces and allows the separation membrane to be used stably for a long period of time, and a thinner layer is preferable because it can reduce the fluid permeation resistance and increase the throughput per unit area. From these perspectives, the thickness of the separation functional layer is preferably in the range of 100 nm to 1000 μm, and more preferably in the range of 200 nm to 10 μm. Here, the thickness of the separation functional layer is defined by measuring the thickness of the thinnest part constituting the separation functional layer with a microscope or the like, and is calculated as the average thickness obtained by analyzing 10 cross-sections of the gas separation membrane.
[0045] The gas separation membrane of the present invention may be a so-called composite membrane having a support for supporting the separation functional layer in addition to the separation functional layer. In the case of a composite membrane, the support for supporting the separation functional layer ensures mechanical strength and durability, preventing damage during actual use and enabling stable operation for a long period of time. In addition, even when high pressure is applied, the support exerts an effect of bearing pressure, and a gas separation membrane capable of operation in a high-pressure environment can be provided.
[0046] Here, the support is not particularly limited as long as it is a material that does not hinder the permeation of gas and also has the function of supporting the separation functional layer, and conventionally known porous materials can be appropriately selected. Examples of porous materials suitable for the support include materials with independent bubbles derived from a sea-island structure, materials with a structure in which multiple particles are connected, nonwoven fabrics in which fibrous materials are folded and appropriately bonded as necessary, and materials with a continuous porous structure in which the voids and the material constituting the support are continuous with each other. These materials are preferably selected appropriately from the viewpoint of not hindering the permeation of fluids and exhibiting the function of supporting the separation functional layer. Among them, materials with a continuous porous structure are more preferable because the voids and the material constituting the support are continuous with each other, so that they do not hinder the permeation of gas, and the material constituting the support has a high effect of dispersing the stress derived from the pressure applied to the separation functional layer, resulting in an increase in the pressure resistance of the gas separation membrane.
[0047] The shape of the gas separation membrane of the present invention is not particularly limited, and can be any shape such as fiber or film. In the case of a fiber shape, there is an advantage that the membrane area per unit volume can be made larger than that of a film shape. In addition, since the resistance to the force applied in the cross-sectional direction is high, it is possible to operate at high pressure, and it is preferable because it is possible to perform gas membrane separation with high efficiency.
[0048] When the gas separation membrane of the present invention has a fibrous shape, the shape of the fiber cross section is not limited at all, and can be any shape such as a multi-leaf cross section such as a round cross section or a triangular cross section, a flat cross section, or a hollow cross section. In particular, when the cross section of the gas separation membrane is a hollow cross section, that is, when the gas separation membrane has a hollow fiber shape, it is possible to control the flow of the supplied gas and the separated gas while providing pressure resistance, which is preferable. When the gas separation membrane has a hollow fiber shape, the higher the hollow ratio, the less the pressure loss is reduced and the less the gas flow is hindered, and the lower the hollow ratio, the higher the pressure resistance is, which is preferable. From these viewpoints, the hollow ratio is preferably in the range of 10 to 90%, and more preferably in the range of 20 to 60%. The hollow fiber may have a single hollow portion or multiple hollow portions.
[0049] The gas separation membrane module of the present invention is a form in which the gas separation membrane of the present invention is housed in a case. The gas separation membrane module is formed with a flow path for controlling the flow of mixed gas and guiding the gas that has permeated the gas separation membrane. It is preferable to use a case or a seal material for the purpose of controlling the flow of these gases. The material of the case is not particularly limited, but is preferably selected appropriately according to the usage environment, such as pressure resistance and heat resistance, and examples of the material include metal, resin, carbon, and composites of these. EXAMPLES
[0050] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited thereto. Evaluations in each of the examples and comparative examples were carried out by the following methods. (Gas separation membrane module) A gas separation membrane module was created by bundling 20 gas separation membranes, each 10 cm long, and storing them in an acrylic pipe (inner diameter 12 mm, wall thickness 3 mm) that served as a case. The ends of the bundled fluid separation membranes were fixed to the inner surface of the case with an epoxy resin adhesive, and both ends of the case were sealed. (Gas separation membrane rupture rate in pressure / decompression tests) Five gas separation membrane modules were prepared for each of the examples and comparative examples, in which it was confirmed that the gas separation membrane did not break during production. The presence or absence of breakage of the gas separation membrane was evaluated as follows. When breakage of the gas separation membrane was visually observed through the acrylic pipe case, it was determined that breakage occurred. When breakage was not visually observed, all but one of the inlets and outlets for the gas to be separated of the gas separation membrane module was sealed, and the entire gas separation membrane module was immersed in water while supplying compressed air of 0.2 MPaG from the inlet and outlet for the gas to be separated that was not sealed. When bubbles were generated from the opening of the gas separation membrane, it was determined that breakage occurred, and when no bubbles were generated, it was determined that no breakage occurred.
[0051] For each gas separation membrane module without rupture, a pressure reduction test was performed in which 10 sets of operations were repeated, with one set being a set of supplying compressed air of 2.0 MPaG to the supply side, holding the state for 1 minute, and then releasing to atmospheric pressure. After the pressure reduction test, the presence or absence of rupture in the gas separation membrane was again determined, and the percentage of modules with ruptures out of the five gas separation membrane modules was taken as the gas separation membrane rupture rate. (Decrease in separation factor after pressure / decompression test) The gas permeation rate of the gas separation membrane module before the pressure reduction test was measured, and the separation factor was calculated based on the ratio of the permeation rates of CO2 and CH4 (CO2 / CH4). The pressure reduction test was then performed, and one of the gas separation membrane modules that had not been broken by the pressure reduction test was selected and the gas permeation rate was measured again to calculate the separation factor. The reduction rate of the separation factor before and after the pressure reduction test was calculated as 1-(separation factor after pressure reduction test / separation factor before pressure reduction test), and a reduction rate of less than 0.1 was judged as "excellent," a reduction rate of 0.1 to less than 0.3 was judged as "good," and a reduction rate of 0.3 or more was judged as "unacceptable."
[0052] The gas permeation rate was measured by measuring the pressure change on the permeation side per unit time for CO2 and CH4 using an external pressure method at a measurement temperature of 25°C in accordance with the pressure sensor method of JIS K 7126-1 (2006). Here, the pressure difference between the supply side and the permeation side was set to 0.11 MPa (82.5 cmHg). Next, the permeation rate Q of the permeated gas was calculated using the following formula, and the separation factor α was calculated as the ratio of the permeation rates of the gases of each component. Note that STP means standard conditions. The membrane area was calculated from the outer diameter and length of the fluid separation membrane in the region contributing to gas permeation.
[0053] Permeation rate Q = [gas permeation flow rate (cm 3 ·STP)] / [Membrane area (cm 2 ) x time (s) x pressure difference (cmHg) The ratio of the gas permeation rates Q of CO2 and CH4, (CO2 permeation rate) / (CH4 permeation rate), was calculated as the separation factor α. [Preparation Example 1] Preparation of 10.0 wt% aromatic polyimide (PI) solution and slurry Aromatic polyimide (hereinafter, aromatic PI) "Matrimid (registered trademark)" 5218 was dissolved in N-methylpyrrolidone (hereinafter, NMP) to prepare a 10.0 wt % aromatic polyimide solution (hereinafter, aromatic PI solution).
[0054] Here, "Matrimid®" 5218 is a condensation product of 3,3',4,4'-benzophenonetetracarboxylic dianhydride and 5(6)-amino-1-(4'-aminophenyl)-1,3,3'-trimethylindane.
[0055] Carbon nanotube powder (FT7000 series, manufactured by CNano) was added to the prepared aromatic PI solution to a volume concentration of 0.30%, followed by the addition of a dispersant. The mixture was stirred and dispersed using a rotation-revolution mixer to prepare a slurry. [Preparation Example 2] Preparation of 10.0 wt% polyacrylonitrile (PAN) solution and slurry Polyacrylonitrile (PAN) (MW 150,000) was dissolved in dimethyl sulfoxide (hereinafter, DMSO) to prepare a 10.0 wt % PAN solution.
[0056] Carbon nanotube powder (FT7000 series, manufactured by CNano) was added to the prepared PAN solution so that the concentration was 0.35 volume %, and then a dispersant was added. The mixture was stirred and dispersed using a rotation-revolution mixer to prepare a slurry. [Preparation Example 3] Preparation of 10.0 wt% cellulose acetate solution and slurry Cellulose acetate (acetylation degree 55%) was dissolved in NMP to prepare a 10.0 wt % cellulose acetate solution. Polyethylene terephthalate (PET) chopped fibers were added to the prepared cellulose acetate solution to a volumetric concentration of 0.40%, and a dispersant was then added. The mixture was stirred and dispersed using a rotation-revolution mixer to prepare a slurry. [Preparation Example 4] Preparation of 8.0 wt% aromatic PI solution and slurry Aromatic PI "Matrimid (registered trademark)" 5218 was dissolved in NMP to prepare a 8.0 wt % aromatic PI solution.
[0057] Carbon nanotube powder (FT7000 series, manufactured by CNano) was added to the prepared aromatic PI solution at a concentration of 0.03 volume %, and a dispersant was then added. The mixture was stirred and dispersed using a rotation-revolution mixer to prepare a slurry. [Example 1] 10 parts by weight of polyacrylonitrile (PAN) (MW 150,000), 10 parts by weight of polyvinylpyrrolidone (PVP) (MW 40,000), and 80 parts by weight of DMSO were mixed and stirred at 100° C. to prepare a spinning dope.
[0058] The obtained spinning dope was cooled to 25°C, and then a concentric triple spinneret was used to simultaneously extrude an 80 wt% aqueous solution of DMSO from the inner tube, the spinning dope from the middle tube, and a 90 wt% aqueous solution of DMSO from the outer tube. The resulting mixture was then introduced into a coagulation bath and wound up on a roller to obtain a raw fiber. The raw fiber was then dried in a circulating hot air dryer to produce a hollow fiber-shaped porous carbon support precursor.
[0059] The porous carbon support precursor was then passed through an electric furnace and heated in an air atmosphere to perform an infusible treatment. The infusible fibers were then carbonized to produce a hollow fiber-shaped porous carbon support. Both the outer and inner surfaces (the surfaces of the hollow portion) of the produced porous carbon support were open, and when the cross section of the hollow fiber was observed, a bicontinuous porous structure was observed.
[0060] A porous carbon support was immersed in the slurry prepared in Preparation Example 1, then pulled out by dip coating, and subsequently immersed in water to remove the solvent, and dried in a circulating hot air dryer to obtain a coated yarn in which aromatic PI containing carbon nanotubes was laminated on the surface of the porous carbon support. The coated yarn was further carbonized at 700°C to produce a gas separation membrane in which a carbon membrane using aromatic PI containing carbon nanotubes as a precursor was laminated on the surface of the porous carbon support.
[0061] At this time, from the three-dimensional data obtained by three-dimensional microscopic photography of the separation functional layer of the gas separation membrane, the content of additive particles was 3.1 volume %, and the average aspect ratio of the additive particles was 1,725. Here, the average aspect ratio was calculated by calculating the average aspect ratio of 10 additive particles that exist independently without contact with other additive particles, and calculating the aspect ratio of each of them. In addition, from elemental analysis using an energy dispersive X-ray spectrometer attached to a transmission electron microscope, the carbon element ratio X of the matrix was 90.3%, and the carbon element ratio Y of the additive particles was 98.6%, and in this case, (|XY| / X) × 100 was 9.2%. The elastic modulus ratio calculated from elastic modulus mapping analysis using an atomic force microscope was 443.
[0062] The rate of breakage of the gas separation membrane in the pressure-decompression test was 0, and the rate of decrease in the separation factor after the pressure-decompression test was "excellent." The evaluation results are shown in Table 1.
[0063] [Table 1]
[0064] [Example 2] A gas separation membrane module was produced in the same manner as in Example 1, except that in the preparation of the slurry in Preparation Example 1, the amount of carbon nanotube powder added was adjusted to 0.02 vol %.
[0065] At this time, the 3D data obtained by 3D microscopy of the separation functional layer showed that the additive particle content was 0.2 volume % and the average aspect ratio of the additive particles was 1,648. Furthermore, elemental analysis using an energy dispersive X-ray spectrometer attached to a transmission electron microscope showed that the carbon element ratio X of the matrix was 90.3% and the carbon element ratio Y of the additive particles was 98.5%, and (|XY| / X) x 100 was 9.1%. The elastic modulus ratio calculated from elastic modulus mapping analysis using an atomic force microscope was 478.
[0066] The rupture rate of the gas separation membrane in the pressure-decompression test was 0.2, and the reduction rate of the separation factor after the pressure-decompression test was "good." The evaluation results are also shown in Table 1. [Example 3] A gas separation membrane module was produced in the same manner as in Example 1, except that the carbonization temperature of the coated yarn was changed to 600°C.
[0067] At this time, the 3D data obtained by 3D microscopy of the separation functional layer showed that the additive particle content was 3.5 volume % and the average aspect ratio of the additive particles was 1,754. Furthermore, elemental analysis using an energy dispersive X-ray spectrometer attached to a transmission electron microscope showed that the carbon element ratio X of the matrix was 86.4% and the carbon element ratio Y of the additive particles was 98.7%, and (|XY| / X) x 100 was 14.2%. The elastic modulus ratio calculated from elastic modulus mapping analysis using an atomic force microscope was 467.
[0068] The rate of breakage of the gas separation membrane in the pressure-decompression test was 0, and the rate of decrease in the separation factor after the pressure-decompression test was "good." The evaluation results are also shown in Table 1. [Example 4] A gas separation membrane module was prepared in the same manner as in Example 1, except that the slurry prepared in Preparation Example 2 was used instead of Preparation Example 1, and the carbonization temperature of the coated yarn was changed to 600°C.
[0069] At this time, from the three-dimensional data obtained by three-dimensional microscopic photography of the separation functional layer, the additive particle content was 3.4 volume %, and the average aspect ratio of the additive particles was 1,580. Furthermore, from elemental analysis using an energy dispersive X-ray spectrometer attached to a transmission electron microscope, the carbon element ratio X of the matrix was 78.2%, and the carbon element ratio Y of the additive particles was 98.5%, and at this time, (|XY| / X) x 100 was 26.0%. The elastic modulus ratio calculated from elastic modulus mapping analysis using an atomic force microscope was 491.
[0070] The rupture rate of the gas separation membrane in the pressure-decompression test was 0.2, and the reduction rate of the separation factor after the pressure-decompression test was "good." The evaluation results are also shown in Table 1. [Example 5] A gas separation membrane module was produced in the same manner as in Example 1, except that in the preparation of the slurry in Preparation Example 1, graphene powder was added instead of carbon nanotube powder.
[0071] At this time, from the three-dimensional data obtained by three-dimensional microscopic photography of the separation functional layer, the additive particle content was 3.2 volume %, and the average aspect ratio of the additive particles was 592. Furthermore, from elemental analysis using an energy dispersive X-ray spectrometer attached to a transmission electron microscope, the carbon element ratio X of the matrix was 90.3%, and the carbon element ratio Y of the additive particles was 98.1%, and at this time, (|XY| / X) × 100 was 8.6%. The elastic modulus ratio calculated from elastic modulus mapping analysis using an atomic force microscope was 341.
[0072] The rate of breakage of the gas separation membrane in the pressure-decompression test was 0, and the rate of decrease in the separation factor after the pressure-decompression test was "good." The evaluation results are also shown in Table 1. [Comparative Example 1] A gas separation membrane module was produced in the same manner as in Example 1, except that the slurry prepared in Preparation Example 3 was used instead of Preparation Example 1, and the coated yarn was not carbonized but was used as a gas separation membrane as is.
[0073] At this time, from the three-dimensional data obtained by three-dimensional microscopic photography of the separation functional layer, the additive particle content was 3.5 volume % and the average aspect ratio of the additive particles was 1,607. Furthermore, from elemental analysis using an energy dispersive X-ray spectrometer attached to a transmission electron microscope, the carbon element ratio X of the matrix was 61.4%, and the carbon element ratio Y of the additive particles was 71.6%, and in this case, (|XY| / X) x 100 was 16.6%. The elastic modulus ratio calculated from elastic modulus mapping analysis using an atomic force microscope was 5.
[0074] The rupture rate of the gas separation membrane in the pressure-reduction test was 0.2, and the reduction rate of the separation factor after the pressure-reduction test was "unacceptable." The evaluation results are also shown in Table 1. [Comparative Example 2] A gas separation membrane module was produced in the same manner as in Example 1, except that in preparation of the slurry in Preparation Example 1, silicon carbide particles were added instead of the carbon nanotube powder.
[0075] At this time, from the three-dimensional data obtained by three-dimensional microscopic photography of the separation functional layer, the additive particle content was 3.1 volume %, and the average aspect ratio of the additive particles was 1. Furthermore, from elemental analysis using an energy dispersive X-ray spectrometer attached to a transmission electron microscope, the carbon element ratio X of the matrix was 90.3%, and the carbon element ratio Y of the additive particles was 49.2%, and in this case, (|XY| / X) × 100 was 45.5%. The elastic modulus ratio calculated from elastic modulus mapping analysis using an atomic force microscope was 186.
[0076] The rupture rate of the gas separation membrane in the pressure-reduction test was 0.6, and the reduction rate of the separation factor after the pressure-reduction test was "unacceptable." The evaluation results are also shown in Table 1. [Industrial Applicability]
[0077] The gas separation membrane module of the present invention is capable of suppressing damage to the gas separation membrane during operation of the gas separation membrane module without impairing the gas separation function, and the use of the module of the present invention is not particularly limited, but it can be preferably used, for example, in a carbon dioxide separation and storage system for exhaust gases from power plants, blast furnaces, etc., removal of sulfur components from gasified fuel gas in integrated coal gasification combined cycle power generation, purification of biogas and natural gas, and purification of hydrogen from organic hydrides.
Claims
1. A gas separation membrane having a separation functional layer at least in a portion thereof, The separation functional layer is composed of a matrix and additive particles, the matrix is made of a carbonized polymer compound, The carbon element ratio of the matrix is 70 atomic % or more and 100 atomic % or less, When the carbon element ratio of the matrix is X (atomic %) and the carbon element ratio of the additive particles is Y (atomic %), (|X-Y| / X)×100 A gas separation membrane, characterized in that the porosity is 30% or less.
2. 2. The gas separation membrane according to claim 1, wherein the additive particles have a higher elastic modulus than the matrix.
3. 3. The gas separation membrane according to claim 1, wherein the separation membrane is a composite membrane.
4. 4. The gas separation membrane according to claim 1, wherein the additive particles are made of an inorganic material.
5. 5. The gas separation membrane according to claim 1, wherein the additive particles have an average aspect ratio of 10 or more.
6. 6. The gas separation membrane according to claim 1, wherein the content of the additive particles in the separation functional layer is 10% by volume or less.
7. 7. The gas separation membrane according to claim 1, wherein the gas separation membrane has a hollow fiber shape.
8. A gas separation membrane module having the gas separation membrane according to any one of claims 1 to 7 housed in a case.
Citation Information
Patent Citations
Production of asymmetric hollow carbon fiber membrane
JP1992193334A
Matrix Membrane Mixed with Pyrolytic Carbon Sieve Particles, and Method of Making and Using the Same
JP2004514546A
Spiral carbon film and method for manufacturing the same
JP2011527231A
Carbon nanotube composite membrane
JP2014237127A
Solvent resistant separation membrane and production method of the same
JP2016047521A